Formula Upah bagi Pengemudi Truk Bahan Bakar Minyak - Henriko Tobing (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2020)
This study tries to offer a formula for calculating a decent wage for fuel truck drivers, especially those transporting fuel oil. The meaning of the word decent is related to meeting the needs of a reasonable life, considerations of driver productivity and safety as well as compliance with applicable wage provisions. The data is based on the monthly salary report at XYZ Company, the results of interviews, and field observations. The multiple linear regression method is used to determine what factors affect the number of wages and the value of the coefficient generated from each variable/factor as the basis for formulating the formula. Related literature review and analysis of applicable wage provisions (wages and overtime pay) are used to strengthen the variables raised in the wage formula. The results showed that several variables did not have a significant effect on wage formation, and the resulting calculation model was able to produce a decent wage level.